Assessing Client Satisfaction with Health Service Delivery under the National Health Insurance Scheme: The Case of Komfo Anokye Teaching Hospital - Hephzibah Okyere-Mensah; Emmanuel Appiah Brempong; Prosper Babon-Ayeng; Ernest Kissi (Advances in Public Health)
Background. Client satisfaction is the direct effect of service delivery and, in essence, the basis for quality improvement in any industry. In health financing, it is a significant determinant of clients’ enrolment in an insurance scheme. Objectives. This study sought to assess client satisfaction with healthcare delivery under the National Health Insurance Scheme (NHIS) at a tertiary facility in Ghana. Methods. A cross-sectional study was conducted among patients attending the outpatient department of the Komfo Anokye Teaching Hospital. Data were collected using structured questionnaires. Questionnaires were administered to 300 purposively selected patients, stratified based on their insurance status. Data obtained were then analysed using mean score ranking and an independent sample t-test. Results. The client satisfaction variable with a high level of satisfaction was observed for physical environment (πins = 3.80; πunins = 3.69). The least rated construct was responsiveness (πins = 2.59; πunins = 2.51). A statistically significant difference in the means between the insured and uninsured was observed for two of the five constructs, namely, communication (πdiff = 0.36; p<0.05) and service availability (πdiff = 0.33; p<0.05). Conclusions. This study advocates for prioritization of measures and policy initiatives aimed at improving responsiveness in healthcare delivery, as the least rated construct. It further draws health providers’ attention to modesty in communication regardless of socioeconomic or insurance status.